Environmental Health Inspection of Sanitation Facilities at the Religious Tourism Tomb of Syaikhona Kholil Bangkalan, East Java - Ilmiyatul Asroriyah; Rachmaniyah; Putri Arida Ipmawati; khambali; Iva Rustanti; Estim, Abentin; Anwar, Taufik (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2025)
Religious tourism is one of the fastest-growing tourism sectors in Indonesia. However, the increasing number of visitors each year, combined with inadequate maintenance of sanitation facilities at religious sites, may elevate the risk of disease transmission. This study aimed to evaluate the condition of sanitation facilities at the Syaikhona Kholil Religious Tourism Site in Bangkalan. A descriptive survey design was employed to assess several key sanitation indicators, including the provision of clean water, wastewater disposal, waste management, toilet facilities, healthcare facilities, fire extinguishing equipment, and educational signage. The findings indicated that the overall sanitation facility score was categorized as